Hubungan Antara Peningkatan Kadar Asam Urat Darah dengan Kejadian Hipertensi di RSUD Sukoharjo - Umami, Helmina Robiyatul; , dr. Retno Suryaningsih, Sp. PD; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background : Hypertension is responsible for target organ damage, but usually people with hypertension do not have any visible sign and symptom, so they dont realize having hypertension. The prevalence of hypertension is increasing by years. Increasing uric acid blood level is one of hypertension risk factor. Uric acid had been known as anti oxydative agent, but recent studies shows increasing uric acid level leads to hypertension. Aim : To know the association between increasing uric acid blood level with incident of hypertension of patient in interna clinic of General Hospital Sukoharjo. Methode : Using cross sectional study design which variable are taken in the same time. Samples are taken from medical records data using simple random sampling. 52 samples divided into 26 hypertension samples and 26 non hypertension. Samples are selected by inclusion and exclusion criteria in this study and recorded uric acid blood level from medical records. Result : 26 samplewith hypertensionhas increasing uric acid blood level (100%), while 26 samplenon hypertensionsamples shows 2 samplshas hiperuricemia (7,7%) and 24 sampleshas normal uric acid (92,3%). The result fromLambda correlation test shows strong correlation (r=0,923) andsignificant correlation (p<0,1) with positive correlation. Conclusion: There is strong correlation between increasing uric acid blood level and incident of hypertension